Spectral and kinetic characteristics of the pulsed cathodoluminescence of a natural IIa-type diamond; Russian Physics Journal; Vol. 50, iss. 1 - Lipatov Е. I.; Lisitsyn V. M. Viktor Mikhailovich; Oleshko V. I. Vladimir Ivanovich; Tarasenko V. F. Victor Fedotovich (2007, 2007)
Title screen